2018
DOI: 10.1039/c8cc02049c
|View full text |Cite
|
Sign up to set email alerts
|

Chiral separation and characterization of triazatruxene-based face-rotating polyhedra: the role of non-covalent facial interactions

Abstract: We constructed a series of novel chiral molecular face-rotating polyhedra (FRP) from two 10,15-dihydro-5H-diindolo[3,2-a:3',2'-c]carbazole (triazatruxene) derivatives and trans-1,2-cyclohexane diamine, and investigated how facial interactions and the positions of substituents determine the diastereoselectivity and geometry of the final assemblies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…For instance, Fujita et al demonstrated that only a 3° difference in the bending angles of two ligands can critically switch achiral Platonic or Archimedean structures into chiral Goldberg polyhedra 15. More recently, our group reported that different positions of aldehyde in triazatruxene (TAT) lead to distinct assembly behaviour and geometry 16. On the other hand, vertices also determined the chirality of FRP.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Fujita et al demonstrated that only a 3° difference in the bending angles of two ligands can critically switch achiral Platonic or Archimedean structures into chiral Goldberg polyhedra 15. More recently, our group reported that different positions of aldehyde in triazatruxene (TAT) lead to distinct assembly behaviour and geometry 16. On the other hand, vertices also determined the chirality of FRP.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our group reported a variety of novel chiral facerotating polyhedra (FRP) 12 consisting of prochiral 2D facial building blocks, such as truxene (Tr) 13 and triazatruxene (TAT). 14 The senses of anticlockwise (A) or clockwise (C) rotations arise when these planar building blocks lose their σh mirror symmetry upon FRP formation, generating a series of diastereoisomeric cages in the one pot reaction (Figure S4). The distribution of the populations of different FRP stereoisomers, instead of being statistically governed, can be biased to favor specific species when interfacial non-covalent interactions are present.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, face-rotating polyhedra constitute a recent class of chiral architecture that can be constructed from chiral or achiral linkers and face-rotating component [59][60][61][62][63][64][65]. The latter can consist of achiral compounds that exhibit two faces with opposite directionalities such as truxene [62][63][64][65], triazatruxene [59,60], and tetraphenylethylene [61]. In particular, the C 3h -symmetric hexa-alkylated truxene derivatives exhibit both clockwise (C; green) and anti-clockwise (A; red) faces that are defined by the rotation of the three sp3 methylene bridges along the C 3 axis (Figure 1a).…”
Section: Introductionmentioning
confidence: 99%